Interleukin-6 on postoperative day three as an early predictor of infections following laparoscopic gastric cancer resection - Yongzhou Huang; Lei Yang; Wenchang Yang; Pei Zhou; Qi Jiang; Weizhen Liu; Yuping Yin; Xiangyu Zeng; Peng Zhang; Kaixiong Tao (BMC Surgery, 2024)
Abstract Background To investigate the role of C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) as early predictors of infectious complications after laparoscopic gastric cancer surgery. Methods Patients who underwent laparoscopic gastric cancer surgery between January 2020 and June 2022 were retrospectively enrolled. IL-6, PCT, and CRP levels were assessed before surgery and on postoperative days (PODs) 3 and 5. Differences in serum IL-6, PCT, and CRP levels between the infected and non-infected groups were compared. The diagnostic accuracy was determined using the area under the receiver operating characteristic curve (AUC). Results A total of 206 patients were enrolled, and 21 patients (10.19%) developed postoperative infections. Serum IL-6, PCT, and CRP levels in the infected group were significantly higher than those in the non-infected group on PODs 3 and 5. IL-6 with an optimal cutoff value of 84.00 pg/mL (AUC 0.84), PCT with an optimal cutoff value of 1.39 ng/mL (AUC 0.80), CRP with an optimal cutoff value of 150.00 mg/L (AUC 0.76) on POD 3 had superior diagnostic accuracy in predicting postoperative infections. Multivariate analysis identified PCT and IL-6 levels on POD 3 as independent risk factors, the AUC of the combination of IL-6 and PCT was 0.89. The Delong test showed no difference between the AUC of IL-6 alone and IL-6 combined with PCT prediction (P = 0.07, Z = 1.81). Conclusions IL-6 level on POD 3 is an excellent predictor of infectious complications following laparoscopic gastric cancer surgery. Patients with IL-6 levels lower than 84.00 pg/mL on POD 3 can ensure safe early discharge with a low probability of infection.